Composition and Stability of the Oxidative Phosphorylation System in the Halophile Plant Cakile maritima - Farhat, Nèjia; Hichri, Sarra; Hildebrandt, Tatjana Manuela; Debez, Ahmed; Braun, Hans-Peter (Frontiers in Plant Science, 2019)
Mitochondria play a central role in the energy metabolism of plants. At the same time, they provide energy for plant stress responses. We here report a first view on the mitochondrial Oxidative Phosphorylation (OXPHOS) system of the halophile (salt tolerant) plant Cakile maritima. Mitochondria were purified from suspension cultures of C. maritima and for comparison of Arabidopsis thaliana, a closely related glycophyte (salt sensitive) plant. Mitochondria were treated with digitonin and solubilized protein complexes were analyzed by 2D Blue native / SDS polyacrylamide gel electrophoresis. The OXPHOS systems of the two compared plants exhibit some distinct differences. C. maritima mitochondria include a very abundant respiratory supercomplex composed of monomeric complex I and dimeric complex III. At the same time the complexes II and IV are of reduced abundance. The stability of the OXPHOS complexes was investigated by combined salt and temperature treatments of isolated mitochondria. ATP synthase (complex V) is of increased stability in C. maritima. Also, the I+III2 supercomplex is present in high abundance during stress treatments. These results give insights into the mitochondrial contribution to the plant salt stress response.